Habitat Selection Patterns Suggest Competition Between Two Forest Rodent Species Along an Elevational Gradient - Ana Maria Benedek; Ioan Sîrbu (Ecology and Evolution)
ABSTRACT Numerous mammal species exhibit dynamic habitat use and selection, choosing the more preferred habitats at low densities when these are more readily available. Habitat selection may also vary along elevation and in relation to other populations' densities, with interspecific competition potentially resulting in habitat segregation. However, little is known about these effects combined. We aimed to evaluate the differential habitat selection by the dominant rodents in relation to intra‐ and interspecific density along an elevational gradient. We used trapping data collected over 7 years (2000–2007) in forests of the Romanian Carpathian Mountains, where Apodemus flavicollis (yellow‐necked mouse) and Clethrionomys glareolus (bank vole) dominated small mammal communities. We hypothesised that (i) habitat segregation facilitates the coexistence of the two species, (ii) because of the differences in their thermic requirements, they have coexisted at high elevations for a shorter time, and therefore their competition is weaker here, resulting in less pronounced habitat segregation and (iii) the abundance of C. glareolus is negatively affected by the abundance of A. flavicollis, which is known to be more competitive. As predicted, the mouse and the vole showed significant opposite responses to most habitat characteristics, indicating habitat segregation as a mechanism of codominance in this relatively continuously forested landscape. As expected, the dissimilarity between their responses was smaller at high elevations, suggesting the recent elevational expansion of A. flavicollis. Contrary to our expectations, the mouse abundance was negatively affected by the vole abundance, but not vice versa. Our study provides insight into the interactions between C. glareolus and A. flavicollis in forests along the elevational gradient, suggesting asymmetrical competition and recent elevational expansion of the latter.